P111 A Workflow Checklist for Improving Management of the Guideline Development Process. (15th August 2013) - Haller, M; Nagler, E; van der Veer, S; Nistor, I; Bolignano, D; Van Biesen, W
Abstract : Background: Keeping track of progress and meeting deadlines can be difficult for organisations that simultaneously develop multiple guidelines involving multiple systematic review teams. Objectives: To improve planning, organising and managing of guideline development projects by creating a standardised workflow checklist. Methods: In a one-day meeting, the five guideline development methodologists, the chairman and the editorial assistant identified the main steps involved in the guideline development process. For each step, we identified specific tasks and ordered them chronologically. All decisions were made based on group consensus. The identified steps and tasks formed the basic elements of the workflow checklist. Results: We identified the need for two separate checklists per guideline development project; one for overall workflow and one for each clinical question covered by the guideline. The overall guideline development workflow checklist comprised 42 tasks organised in 11 sequential steps, including items such as topic selection, composition of the guideline development group, and framing the questions. For each clinical question we identified 27 tasks organised in 8 sequential steps, excluding steps already covered by the overall workflow. Discussion: This workflow checklist represents a first step in developing a standardised project management strategy to improve efficient management of the guideline development process. Further development of this tool involves selecting appropriate software for practical implementation applicable not only for our own means but also for those of other groups. Implications for Guideline Developers/Users: We believe developing a standardised workflow checklist will improve efficient management of guideline development and allows transparent and up-to-date communication of its progress.